Assessment of Knowledge and Attitudes toward Medical Waste Segregation among Nursing Students: A Case Study at University in Vietnam - Trang, Trần Thị Thu; Đặng, Vu Ha (PT. Riset Press International, 2025)
Medical waste management is a critical component in safeguarding public health and environmental sustainability. It is also an essential factor in ensuring effective and safe operations at healthcare facilities, requiring a well-trained and competent workforce. This study aims to assess the current level of knowledge and attitudes of final-year nursing students at Nam Dinh University of Nursing, Vietnam, regarding medical waste segregation. A cross-sectional survey was conducted among 240 final-year nursing students. Data were collected using a self-administered questionnaire comprising three sections: personal demographic information, knowledge of medical waste segregation, and attitudes toward the practice. Descriptive statistics and inferential analyses, including t-tests and chi-square tests, were used to explore associations between knowledge and attitudes and factors such as gender, academic performance, and self-study habits. Results: Only 41.3% of students demonstrated adequate knowledge regarding medical waste segregation, and up to 65% exhibited negative or non-positive attitudes toward the issue. Academic performance and self-directed learning habits were significantly associated with both knowledge and attitudes. Students with higher academic achievement and regular self-study routines tended to have better knowledge and more positive attitudes. The findings reveal that both knowledge and attitudes toward medical waste segregation among nursing students at Nam Dinh University of Nursing remain limited. Enhancing the nursing curriculum, raising awareness, and providing specialized training sessions on medical waste management are essential steps to strengthen public health protection efforts.